1996
DOI: 10.1149/1.1836387
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Nickel‐Iron Alloys in Molten Carbonate

Abstract: Cyclic voltammetry experiments show that the corrosion behavior of binary nickel-iron alloys shows a gradual change from iron-like behavior to nickel-like behavior. The behavior of the 50 and 75% iron alloy is similar to the behavior of pure iron, the behavior of the 10% iron alloy is similar to the behavior of pure nickel, but during a cathodic scan, some significant differences can be observed. At an iron content of approximately 25%, characteristics of iron-rich and nickel-rich behavior could be observed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…LiFeO 2 has a cubic structure in which Li and Fe atoms randomly occupy the octahedral sites in a cubic close packing of oxygen atoms. 20,21 NiO also has a cubic structure, Du et al found that NiO has a uniform and dense octahedron structure in Li 2 CO 3 -Na 2 CO 3 -K 2 CO 3 melt at 650 • C. 22 As the lattice parameters of NiO and LiFeO 2 are relatively similar, they tend to form solid solutions, which is in good agreement with the study of Vossen et al 17 After 100 h anodic polarization, the oxide particles are still in size of ∼1-2 μm with octahedral morphology as shown in Figures 4c and 4d. It suggests that the oxide film is physically and chemically stable during anodic polarization.…”
Section: Formation Of Oxide Film On Ni11fe10cu By Potentiostatic Pola...supporting
confidence: 79%
See 2 more Smart Citations
“…LiFeO 2 has a cubic structure in which Li and Fe atoms randomly occupy the octahedral sites in a cubic close packing of oxygen atoms. 20,21 NiO also has a cubic structure, Du et al found that NiO has a uniform and dense octahedron structure in Li 2 CO 3 -Na 2 CO 3 -K 2 CO 3 melt at 650 • C. 22 As the lattice parameters of NiO and LiFeO 2 are relatively similar, they tend to form solid solutions, which is in good agreement with the study of Vossen et al 17 After 100 h anodic polarization, the oxide particles are still in size of ∼1-2 μm with octahedral morphology as shown in Figures 4c and 4d. It suggests that the oxide film is physically and chemically stable during anodic polarization.…”
Section: Formation Of Oxide Film On Ni11fe10cu By Potentiostatic Pola...supporting
confidence: 79%
“…After 40 h polarization, new diffraction peaks related to NiO (PDF#04-0835) and LiFeO 2 (PDF#70-2711) appear. 17 It was reported that NiO, NiFe 2 O 4 and CuO composite film formed on Ni11Fe10Cu alloy by air oxidation, 14 and NiO, NiFe 2 O 4 and Cu three-layered scale formed on the alloy by electrochemical oxidation in binary carbonates of Na 2 CO 3 -K 2 CO 3 . 14 Interestingly, no NiFe 2 O 4 and CuO was observed in the oxide film according to the XRD patterns.…”
Section: Formation Of Oxide Film On Ni11fe10cu By Potentiostatic Pola...mentioning
confidence: 99%
See 1 more Smart Citation
“…Barrier layer may be formed by a dissolution-precipitation mechanism and/or a solid state mechanism. The results of x-ray diffraction analysis [6] MO n/2 + n/2 CO 2 + ne (7) in the case of carbonate melt and the investigated alloys (1,2,3), it can be proposed, as in previous works [8,14,15], that the oxidation and passivation of the alloys may proceed according to the following reactions:…”
Section: Methodsmentioning
confidence: 99%
“…The temperature was between 85-95°C. By varying the amount of cobalt sulphate in the bath different ternary alloys of Ni-Co-P can be obtained [19]. The Co-Ni encapsulated SS304 was rinsed with deionized water and subsequently dried at 65°C for 4 hours.…”
Section: Methodsmentioning
confidence: 99%